Comparing Cost Leadership Strategy with Differentiation Strategy towards Firm Performance on Jakarta Islamic Index - Surono surono; Tulus Suryanto; Erike Anggraini (The Winners, 2020)
The research aimed to examine the effect of cost leadership strategy and differentiation strategy on company’s performance. It was conducted in companies listed in the Jakarta Islamic Index from 2014 to 2018. Purposive sampling was used to obtain samples from 12 companies. Analysis was done by multiple linear regression with the help of the IBM SPSS 23 statistical program for windows with a quantitative descriptive approach. The results show that the cost leadership strategy influences company’s performance compared to differentiation strategy. The implementation of a low-cost strategy is significantly relevant to the condition of people who are sensitive to price and are not much aware about brand products in decision making. The design of a unique item model does not determine success in marketing a product, the relative price offered is quite high and only in certain market segments the product is of public interest. Product quality is defeated by the quantity of goods, people prefer how much goods are obtained than the durability of the products consumed.